Exosome as a target for cancer treatment. (24th February 2022) - Nafar, Samira; Nouri, Negar; Alipour, Maedeh; Fallahi, Jafar; Zare, Fateme; Tabei, Seyed Mohammad Bagher
Abstract : Exosomes are small vesicles covered by a lipid bilayer, ranging in size from 50 nm to 90 nm, secreted by different cell types in the body under normal and pathological conditions. They are surrounded by cell-segregated membrane complexes and play a role in the pathological and physiological environments of target cells by transfer of different molecules such as microRNA (miRNA). Exosomes have been detected in many body fluids, such as in the amniotic fluid, urine, breast milk, blood, saliva, ascites, semen, and bile. They include proteins, lipids, and nucleic acids such as DNA, RNA, and miRNA, which have many functions in target cells under pathological and physiological conditions. They participate in pathological processes such as tumor growth and survival, autoimmunity, neurodegenerative disorders, infectious diseases, inflammation conditions, and others. Biomarkers in exosomes isolated from body fluids have allowed for a more precise and consistent diagnostic method than previous approaches. Exosomes can be used in a variety of intracellular functions, and with advances in molecular techniques they can be used in the treatment and diagnosis of many diseases, including cancer. These vesicles play a significant role in various stages of cancer. Tumor-derived exosomes have an important role in tumor growth, survival, and metastasis. In contrast, the use of stem cells in cancer treatment is a relatively new scientific area. We hope to address targeted use of miRNA-carrying exosomes in cancer therapy in this review paper.